Phytochemistry, traditional uses and cancer chemopreventive activity of Amla (Phyllanthus emblica): The Sustainer - Ekta Singh, Sheel Sharma, Ashutosh Pareek, Jaya Dwivedi, Sachdev Yadav, Swapnil Sharma (Journal of Applied Pharmaceutical Science)
Ayurveda, which is the oldest health system in the world, appreciates and uses amla to treat a host of diseases and promote positive health. Amla [Emblica officinalis, or emblic myrobalan], is called amalaki in Sanskrit. It is extensively used as a rejuvenator in ayurveda. It is also used widely in combination with other two [chebulic and belleric] myrobalans [fruit-bearing plant species] as triphala. Amla is indeed, the key ingredient in the popular ayurvedic recipe, Chyavanaprasha. More than anything, it may be called as "King of Rasayana" [rejuvenation], owing to its multiple health benefits. Phyllanthus emblica or Indian gooseberry (Amla) possesses a vastethnomedical history and represents a phytochemical reservoir of heuristic medicinal value. It is one of the oldest oriental medicines mentioned in Ayurveda as potential remedy for various ailments. The fruit is rich in quercetin, phyllaemblic compounds, gallic acid, tannins, flavonoids, pectin and vitamin C and also contains various polyphenolic compounds. A wide range of phytochemical components including terpenoids, alkaloids, flavonoids, and tannins have been shown to posses’ useful biological activities. Many pharmacological studies have demonstrated the ability of the fruit shows antioxidant, anticarcinogenic, antitumour, antigenotoxic, antiinflammatory activities, supporting its traditional uses. In this review, we have focused our interest on phytochemistry, traditional uses, cancer chemopreventive activity of Phyllanthus emblica both in vivo and in vitro. In view of its reported pharmacological properties and relative safety, P. emblica could be a source of therapeutically useful products.
Keywords: Phyllanthus emblica, Medicinal herb, anticarcinogenic, antitumor activity.